Passively conducted vibration sensing with fiber bragg gratings - Mohanty, Lipi (2018)
Measuring vibrations is a common method of monitoring the integrity of structures and heavy machinery, that are subject to dynamic loads. Strong vibrations for prolonged periods of time can be caused by various sources, such as trains, motors and heavy machinery. These strong vibrations should be identified and managed to ensure operational safety. This study proposes a flexible metal beam sensor with a fiber Bragg grating (FBG) mounted on the surface to measure the vibrational frequency. We present a sensor for measuring the vibrational frequencies on-site by placing the beam so that it makes physical contact with the vibrating body. The sensor has been tested in the range of 50–200 Hz. The sensing beam can detect the vibrations that are induced in other metallic bodies where there are metallic structures of low stiffness to conduct the vibration. The results show that the sensing beam is capable of detecting the frequency of forced vibrations from its periphery when placed in different orientations.